Research data management compliance: is there a bigger role for university libraries?. Issue 4 (2nd October 2018) - Shelly, Marita; Jackson, Margaret
ABSTRACT: This article explores how 13 Australian universities are assisting their researchers to manage the growing expectation to make research data more accessible. It identifies which university groups are supporting staff with research data management (RDM) activities and queries whether university libraries might have a bigger role to play in this space. We found that there was not a consistent approach to RDM at the 13 universities and that while there was generally strong encouragement to store research data securely during and after the project, there was overall a lack of practical support in how to undertake this activity. From our findings, a question of whether library staff have the appropriate experience, training and professional development to enable academic libraries in Australia to expand their RDM role arises and warrants further research.